ANALISIS PENGARUH KEPUASAN TERHADAP COORPORATE TRUST DAN LOYALTY INTENTION PASIEN DI KLINIK ELANG MERAH - Lalu Harianto Sutrisno (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
: There are many health services facilities in Indonesia, they are able to give best quality service for people. The total of hospital and community health centre which are able to serve only five percent the total population, and this condition can influent the quality service that the people needs. The existence of private clinics are one the best solution to solve the problem. The according to health minister, clinic is one facility health service that conduct personal health service like based medical or specialis to promotive, preventive, curative and rehabilitative. It is has been proved that Elang Merah Clinic has been operating for five years and do it’s best to serve the community. The services are full satisfaction for patient, so that patient will come from time to time to check their health. Many ways to do like the clinic, increasing the room, knowledge and skill of medic and nurse, all of then are the aim to increase satisfaction, trust of clinic and loyalty intention to patient. Loyalty intention to the patient is the aim of clinic management, with the loyalty intention, the clinic will get value, the patien will come again to spend their money to have the best quality health service provide. Key word : satisfaction, coorporate trust, loyalty intention.